The role of chick Ebf genes in the mediolateral patterning of the somites. Issue 11 (13th November 2019) - EL‐Magd, Mohammed A.; Elsayed, Shafika A.; El‐Shetry, Eman S.; Abdelfattah‐Hassan, Ahmed; Saleh, Ayman A.; Allen, Steve; McGonnell, Imelda; Patel, Ketan
Summary: This study was conducted to check whether the three chick Early B‐cell Factor ( Ebf ) genes, particularly cEbf1, would be targets for Shh and Bmp signals during somites mediolateral (ML) patterning. Tissue manipulations and gain and loss of function experiments for Shh and Bmp4 were performed and the results revealed that cEbf1 expression was initiated in the cranial presomitic mesoderm by low dose of Bmp4 from the lateral mesoderm and maintained in the ventromedial part of the epithelial somite and the medial sclerotome by Shh from the notochord; while cEbf2/3 expression was induced and maintained by Bmp4 and inhibited by high dose of Shh. To determine whether Ebf1 plays a role in somite patterning, transfection of a dominant‐negative construct was carried out; this showed suppression of cPax1 expression in the medial sclerotome and upregulation and medial expansion of cEbf3 and cPax3 expression in sclerotome and dermomyotome, respectively, suggesting that Ebf1 is important for ML patterning. Thus, it is possible that low doses of Bmp4 set up Ebf1 expression which, together with Shh from the notochord, leads to establishment of the medial sclerotome and suppression of lateral identities. These data also conclude that Bmp4 is required in both the medial and lateral domain of the somitic mesoderm to keep the ML identity of the sclerotome through maintenance of cEbf gene expression. These striking findings are novel and give a new insight on the role of Bmp4 on mediolateral patterning of somites.